The proteome of mouse cerebral arteries - Badhwar, AmanPreet (Nature Publishing Group, 2014)
The cerebral vasculature ensures proper cerebral function by transporting oxygen, nutrients, and other substances to the brain. Distribution of oxygenated blood throughout the neuroaxis takes place at the level of the circle of Willis (CW). While morphologic and functional alterations in CW arteries and its main branches have been reported in cerebrovascular and neurodegenerative diseases, accompanying changes in protein expression profiles remain largely uncharacterized. In this study, we performed proteomics to compile a novel list of proteins present in mouse CW arteries and its ramifications. Circle of Willis arteries were surgically removed from 6-month-old wild-type mice, proteins extracted and analyzed by two proteomics approaches, gel-free nanoLC-mass spectrometry (MS)/MS and gel-based GelLC-MS/MS, using nanoAcquity UPLC coupled with ESI-LTQ Orbitrap XL. The two approaches helped maximize arterial proteome coverage. Six biologic and two technical replicates were performed. In all, 2,188 proteins with at least 2 unique high-scoring peptides were identified (6,630 proteins total). Proteins were classified according to vasoactivity, blood–brain barrier specificity, tight junction and adhesion molecules, membrane transporters/channels, and extracellular matrix/basal lamina proteins. Furthermore, we compared the identified CW arterial proteome with the published brain microvascular proteome. Our database provides a vital resource for the study of CW cerebral arterial protein expression profiles in health and disease.